THE EFFECT OF MERAPI VOLCANO ERUPTION ON LAND USE CHANGE AND AGRICULTURE - Jujuk Juhariah; Zue-er Chen; Li-Fang Yu (AGROTECH Research Journal, 2020)
There are four purposes of this research. To know the effect of Merapi Volcano eruption on land use change and agriculture. Identify the most suitable crops in for affected areas. To advise the Sleman government about more suitable land use, thus increasing the local potential. To help the farmers overcome negative effects of the eruption as soon as possible. This research conducted in Cangkringan District, Sleman Regency, Yogyakarta Province, Indonesia and only focused on three eruptions, 2001, 2006, and 2010. The methodologies to do this research are interviews, questionnaires, observations, collect data from Sleman Regency Government, and study the satellite images from the United States Geological Survey. The researcher interviews seven government officers and uses 300 questionnaires to get the information from the farmers. The researcher observes the study site and distributes the questionnaire at the same time. Data from Sleman Regency government is about the farming product of Cangkringan and maps of Sleman Regency. This research use satellite image from Landsat 7 ETM+ starts from 2000-2011 in path 120 and row 65. The result shows that the eruption in 2001 and 2006 did not give significant effect on land use change and agriculture in Cangkringan. The eruption in 2010 gives huge effect to the land use and agriculture in Cangkringan. Agriculture is the most suitable land use in Cangkringan. In addition, the suitable crops for the areas around Merapi Volcano are corn, peanut, spring onions, and onions that resistant to silica content in the fresh volcanic soil. To improve the local potential and improve the socio-economic level for people in Cangkringan, a combination of agriculture and recreation industry in Cangkringan can be use.